2020
DOI: 10.1007/s00392-020-01659-0
|View full text |Cite
|
Sign up to set email alerts
|

Cryoballoon pulmonary vein isolation-mediated rise of sinus rate in patients with paroxysmal atrial fibrillation

Abstract: Background Modulation of the cardiac autonomic nervous system by pulmonary vein isolation (PVI) influences the sinoatrial nodal rate. Little is known about the causes, maintenance and prognostic value of this phenomenon. We set out to explore the effects of cryoballoon PVI (cryo-PVI) on sinus rate and its significance for clinical outcome. Methods and results We evaluated 110 patients with paroxysmal atrial fibrillation (AF), who underwent PVI using a second-generation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…Our study confirms the significant impact of PVI on cardiac autonomic function with a mean heart rate increase by over 10 bpm at POST which is in line with previously published results [ 5 , 7 9 ]. This effect is suggested to be induced by parasympathetic denervation owing to PVI ablation [ 6 , 7 ] which is known to influence the sinus rate, the atrial refractory period and atrioventricular conduction [ 14 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study confirms the significant impact of PVI on cardiac autonomic function with a mean heart rate increase by over 10 bpm at POST which is in line with previously published results [ 5 , 7 9 ]. This effect is suggested to be induced by parasympathetic denervation owing to PVI ablation [ 6 , 7 ] which is known to influence the sinus rate, the atrial refractory period and atrioventricular conduction [ 14 ].…”
Section: Discussionsupporting
confidence: 93%
“…The autonomic nervous system has been shown to play a pivotal role in the pathogenesis of atrial fibrillation [ 3 ]. In this regard, it has been shown that patients with atrial fibrillation and a low resting sinus heart rate prior to ablation seem to carry a higher risk for recurrence of atrial fibrillation post-ablation [ 4 , 5 ]. It has been suggested that catheter ablation has an attenuating effect on parasympathetic activity [ 6 , 7 ] leading to an increased resting heart rate post-ablation.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, AF has been associated with bradycardia and need for PPM implantation. 43 , 44 , 45 Especially in patients with sinus node dysfunction, successful treatment of AF and restoration of sinus rhythm may manifest in severe bradycardia requiring PPM implantation. 4 , 24 In our study, we also found a significantly higher percentage of 1 year PPM implantation after HTX in patients with AF before and ≤ 30 days after HTX (5.5%) as well as in patients without AF before HTX but with AF ≤ 30 days after HTX (6.7%) indicating an association between post‐transplant AF and the need for PPM implantation after HTX.…”
Section: Discussionmentioning
confidence: 99%
“…Although this is a single case, together with the earlier case report, 13 , 14 it suggests that ablation, rather than permanent pacing, may be a better choice for the initial treatment of asymptomatic, slow AF with SAND and AVND. 15 Table 2 lists the advantages and disadvantages of ablation vs pacing in patients with AF and AVND.…”
Section: Discussionmentioning
confidence: 99%